Effect of Controlled-release Nitrogen Fertilizer on Methane Emission from Paddy Field Soil. (2016) - Anitha, K.; Bindu, G.
Abstract: An experimental study was conducted to investigate the effect of Controlled Release Nitrogen Fertilizer on CH4 emission from a rice paddy field soil using pot experimental setup. The experiment is designed with three fertilizer types, i.e., controlled-release nitrogen fertilizer (Neem oil coated urea) and urea (U) and organic fertilizers like Gliricidia sepium, cowpea, Farmyard manure etc. There are two rice cultivars Uma and Jyothy were used for the pot experiment. Each experiment replicate triply. Methane flux was measured at different growth stages for the two rice cultivar by one-time application of CRNF compared with Urea and Organic fertilizer. The methane emission was noted at different rice growth stages. Finally the total CH4 emission from the cultivar is also calculated. CH4 emission was decreased at vegetative stage, gradually increased at reproductive stage and decreased at grain filling to maturity. Methane emission was higher from Heading to flowering, accounting for 35.21% to 41.53% of total cumulative emission. CRNF significantly affect the biometric characters like tiller number, plant height, biomass, and yield in rice by using CRNF. Rice yields increased by 11.43 and 11.11% for Uma and Jyothy rice respectively.